A Critical Review on the Development Approaches in Iran: Solutions of Promoting Internal Production Focusing on Capabilities Approach in the Framework of Resistive Economy Discourse - Hamid Padash; bahman khodapanah (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
One of the most important components of implementing resistive economy is to pay special attention to the production of primary commodities and fundamental products based on knowledge-based economy. In order to realize the resistive economy policies in Iran, there is a need to move from low-tech level to high- tech level productions. Business development in the sophisticated exports requires the development of technical and institutional capabilities. Hence, the present study aims to investigate and introduce the mechanisms of production of complex and sophisticated commodities in Iran according to the capability approach. After reviewing the research literature, using the complexity atlas, proposed by Hausmann and Hidalgo (2013), Iran’s position in world complex products has been analyzed. Results show that Iran has not been successful in producing complex commodities. Iran’s production and exports are often related to simple commodities, and like many other developing countries, Iran has suffered from acquiescence trap. Finally, policy suggestions have been made to improve the level of product complexity.